The guilty pleasures of bigotry: ethnic stereotypes in Trevor Nunn's Merchant of Venice and Dave Chappelle's pixie sketches. (2nd July 2016) - O'Rourke, James
ABSTRACT: Trevor Nunn's 1999 Royal National Theatre production of The Merchant of Venice and Dave Chappelle's "pixie sketches", produced in 2005 for Comedy Central USA, addressed the same challenge: how does one present ethnic stereotypes in a way that undermines those stereotypes rather than reinforcing them? The different representational strategies adopted by Nunn and Chappelle illustrate the different conventions that govern the representation of ethnicity in high and popular culture. Nunn downplayed the most stereotypical elements of Merchant and guided viewers towards a clear and obvious moral choice. He updated the setting of the play to Weimar Germany, evoking a strong sense of specific social context and prompting the audience to identify with Shylock as the victim of a toxic culture. Chappelle presented a series of hyperbolic racist caricatures that tempted his audience to make the wrong choice. The pixie sketches both solicit and chastise laughter, potentially making viewers aware of their momentary indulgence in the guilty pleasures of bigotry. In Nunn's Merchant, the antidote to racism is empathy, and the audience is reassured of its moral probity; in Chappelle's pixie sketches, the antidote to racism is critical reflection, and audience members are left wondering whether they really should have laughed at Chappelle being called a "big-lipped bitch". Reading Merchant through the rough representational logic of the pixie sketches can offer a richer sense of Shakespeare's treatment of ethnic stereotyping than can be found within the conventions of the naturalistic theatre of empathy.